The Art Experience of the Indonesian People in the Industry 4.0 Era (A Philosophical View) - Priskardus Hermanto Candra; Azih Zunaidah (Soshum: Jurnal Sosial dan Humaniora, 2020)
For Indonesian people, the world of art is an integral part of life. Art has become their identity since the ancient time. It is because art and its products are born from the appreciation of everyday life. Art philosophy is inseparable from the meaning of daily life. The more a society produces art with high values and tastes, the more reflective capacity they have to explore life. This reflective ability has actually helped enliven the development era which has increasingly undergone fundamental changes (disruption) in all fields. Entering the era of industrial revolution 4.0, now the world of art and its meaning are slowly distorted. Revolution 4.0 dragged art into capitalism and ended in obscurity of identity. Gadamer's study of how to view art as a game, symbol and festival becomes an interruption to restore the meaning of art in its place. Gadamer's art criticism is also very relevant for Indonesian people. This criticism is an opportunity for Indonesians to reinterpret the spirit of art in them. Understanding art means immersing in one’s self-identity as a true Indonesian to become more authentic.